Nothing daunted : the unexpected education of two society girls in the West - Wickenden, Dorothy (Scribner, 2011)
"A captivating full-length book derived from a widely read and much beloved New Yorker piece about Wickenden's grandmother and her grandmother's best friend who left their affluent East Coast lives to "rough it" as teachers in the wilds of Colorado in 1916"-- Provided by publisher.